A Case Study on Front Office Staff Service Quality Improvement as New Trends for Best Customer Satisfaction in Hotel Radisson Blu Kaushambi, Ghaziabad (Global Journal of Management and Business Research, 2022)
Customer satisfaction is defines that how customers are satisfied with a company's products, services, and capabilities. Customer satisfaction information, including surveys that helps the department to findout the actual problem and start working on it overall at the end it increases the overall value of the hotel
Keywords: customer preference; fine dining restaurant; quick service restaurant